2021
DOI: 10.1021/acs.inorgchem.0c03755
|View full text |Cite
|
Sign up to set email alerts
|

Largely Color-Tuning Prompt and Delayed Fluorescence: Dinuclear Cu(I) Halide Complexes with tert-Amines and Phosphines

Abstract: Luminescent copper­(I) halide complexes with bi- and tridentate rigid ligands have gained wide research interests. In this paper, six tetracoordinate dinuclear copper­(I) halide complexes, Cu2X2(ppda)2 [ppda = 2-[2-(dimethylamino)­phenyl­(phenyl)­phosphino]-N,N-dimethylaniline, X = I (1), Br (2), Cl (3)] and Cu2X2(pfda)2 [pfda = 2-[2-(dimethylamino)-4-(trifluoromethyl)­phenyl­(phenyl)­phosphino]-N,N-dimethyl-5-trifluoromethylaniline, X = I (4), Br (5), Cl (6)], were successfully prepared and systematically cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…While for singlet harvesting, the molecules have to show efficient thermally activated delayed fluorescence (TADF) at ambient temperature. Examples are found among Cu(I), Ag(I), Au(III), W(VI) and Zn(II) complexes [ 7 , 9 , 10 , 11 , 12 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ] or specifically designed organic molecules [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ,…”
Section: Introductionmentioning
confidence: 99%
“…While for singlet harvesting, the molecules have to show efficient thermally activated delayed fluorescence (TADF) at ambient temperature. Examples are found among Cu(I), Ag(I), Au(III), W(VI) and Zn(II) complexes [ 7 , 9 , 10 , 11 , 12 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ] or specifically designed organic molecules [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ,…”
Section: Introductionmentioning
confidence: 99%
“…Such derivatives offer particularly appealing prospects for future developments, not only due to the relatively high abundance and low cost of copper offering a competitive alternative to the well-known phosphorescent compounds based on expensive heavy metal complexes, but also due to the various photophysical properties these Cu( i ) complexes exhibit. 1–46 Indeed, emission covering the full visible light spectrum has been reported for such compounds, combined with a large diversity of radiative relaxation processes, including very efficient Thermally Activated Delayed Fluorescence (TADF) processes. 7,8,13–36 In such complexes presenting TADF properties, spatially well-separated HOMO and LUMO induce a small energy gap between the lowest energy singlet–triplet states.…”
Section: Introductionmentioning
confidence: 99%
“…1–46 Indeed, emission covering the full visible light spectrum has been reported for such compounds, combined with a large diversity of radiative relaxation processes, including very efficient Thermally Activated Delayed Fluorescence (TADF) processes. 7,8,13–36 In such complexes presenting TADF properties, spatially well-separated HOMO and LUMO induce a small energy gap between the lowest energy singlet–triplet states. This enables a thermal population of the lowest energy excited singlet state (S 1 ) from the lowest energy triplet excited state (T 1 ) via a reverse intersystem crossing (RISC).…”
Section: Introductionmentioning
confidence: 99%
“…5–7 Previous reports have indicated that Cu( i )-based complexes with different types of coordinated ligands are able to achieve remarkable luminescence characteristics, including room temperature phosphorescence (RTP) and thermally activated delay fluorescence (TADF). 8–12 Such cuprous complexes show great potential for applications in optoelectronic devices and luminescence-based sensors. 13–17 The d 10 configuration of Cu( i ) tends to favor the tetrahedral geometry and extensive studies on Cu( i )-based emitters show that the typical mononuclear four-coordinated Cu( i ) complexes generally exhibit inferior luminescence properties.…”
Section: Introductionmentioning
confidence: 99%